2015
DOI: 10.1016/j.jcps.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

To do or to have, now or later? The preferred consumption profiles of material and experiential purchases

Abstract: Extending previous research on the hedonic benefits of spending money on doing rather than having, this paper investigates when people prefer to consume experiential and material purchases. We contend that the preferred timing of consumption tends to be more immediate for things (like clothing and gadgets) than for experiences (like vacations and meals out). First, we examine whether consumers exhibit a stronger preference to delay consumption of experiential purchases compared to material goods. When asked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 34 publications
(67 reference statements)
2
56
2
2
Order By: Relevance
“…We would contend that, in this respect, Rick Blaine is unlike most consumers-at least when it comes to experiences. Consistent with the idea that people savor the wait for experiential purchases, Kumar and Gilovich (2014c) recently found that whereas material purchases tend to prompt a "give-it-to-me-now" mind-set, consumers often prefer to delay their consumption of experiences. This makes them more patient when it comes to experiential consumption: when faced with intertemporal tradeoffs, they tend to prefer a better experience later than a lesser experience now-a pattern that is not true for comparable material purchases.…”
Section: Making Plans That Far Ahead: the Prospective Benefits Of Expmentioning
confidence: 74%
See 1 more Smart Citation
“…We would contend that, in this respect, Rick Blaine is unlike most consumers-at least when it comes to experiences. Consistent with the idea that people savor the wait for experiential purchases, Kumar and Gilovich (2014c) recently found that whereas material purchases tend to prompt a "give-it-to-me-now" mind-set, consumers often prefer to delay their consumption of experiences. This makes them more patient when it comes to experiential consumption: when faced with intertemporal tradeoffs, they tend to prefer a better experience later than a lesser experience now-a pattern that is not true for comparable material purchases.…”
Section: Making Plans That Far Ahead: the Prospective Benefits Of Expmentioning
confidence: 74%
“…As a result, with a few exceptions (Carter & Gilovich, 2010;Kumar & Gilovich, 2014c;Kumar, Killingsworth, et al, 2014;Nicolao et al, 2009;Weidman & Dunn, 2014), nearly all studies to date have examined people's retrospective evaluations of material and experiential purchases. This dovetails with research on psychological well-being generally, which has tended to focus on global, retrospective evaluations of happiness rather than in-the-moment experiences of pleasure (Kahneman & Riis, 2005).…”
Section: What Type Of Happiness and When?mentioning
confidence: 99%
“…In some studies, furthermore, we have coded purchases in terms of subjective appeal, and our results are also not an artifact of participants thinking of inherently more appealing experiences than possessions. Finally, many of the effects reported in this program of research—more satisfaction derived from experiences than from possessions, more regrets of inaction for experiences rather than possessions, fewer comparisons to other purchases when it comes to experiences rather than possessions—have been obtained when the very same purchase is framed in either material or experiential terms (Carter & Gilovich, 2010, 2012; Kumar & Gilovich, under review‐c; Mann & Gilovich, in preparation; Rosenzweig & Gilovich, 2012). Participants are clearly not thinking of an extraordinary experience and a mundane material item in these studies.…”
Section: Populations and Methodsmentioning
confidence: 96%
“…In addition, gratitude and learning mindfulness skills are possible to reduce materialist goals and mitigate the negative effects of materialism (Polak & McCullough, 2006;Wang et al, 2017a). Some studies have also found that allocating disposable money to experiential consumption (tourism, watching performances) will be more enjoyable, satisfaction and happiness than investing in material wealth (clothing, jewelry) (Kumar & Gilovich, 2016). This is because experience buyers mainly evaluate material wealth based on their functional utility and the satisfac-Psychology tion of basic human needs.…”
Section: Activate the Intrinsic Goalmentioning
confidence: 99%